Kinetics of Oven Drying of Ocimum basilicum Leaves Harvested at Different Ages of Maturity - Badila, Jeantia Michaely Matoko; Biassala, Eliane Thérèse; Ngounga, Célestine Kiminou; Gobet, Danielle; Silou, Thomas (European Journal of Applied Sciences, 2024)
Drying is a unitary operation that involves the simultaneous transfer of heat and humidity to reduce the water content of products to a safe level. This work therefore aims to study the characteristics of drying in an oven through the effect of temperature and drying time on Ocimum basilicum leaves harvested at different stages of maturity and to adapt the drying data into ten mathematical models to determine which one is best validated by experimental data. The leaves studied were collected at well-defined time intervals corresponding to the level of growth or maturity of the plants, i.e. one month, two months and three months. Drying was carried out using a natural convection oven at temperatures of 70, 80 and 90 °C. The water content varied from 80 to 86% depending on the age of the leaves. The drying speed was rapid at the beginning of the process and decreased after 60 min. The coefficient of determination and chi-square were used as statistical parameters for comparing the accuracy of the models. The Wang and Sing and Exponential models gave a better fit and better validated the experimental data compared to the other models whatever the temperature and age of the leaves.